2016
DOI: 10.15517/rbt.v64i1.18223
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus and Penicillium (Eurotiales: Trichocomaceae) in soils of the Brazilian tropical dry forest: diversity in an area of environmental preservation

Abstract: Soil is a complex biological system that plays a key role for plants and animals, especially in dry forests such as the Caatinga. Fungi from soils, such as Aspergillus and Penicillium, can be used as bioindicators for biodiversity conservation. The aim of this study was to isolate and identify species of Aspergillus and Penicillium in soil, from the municipalities of Tupanatinga and Ibimirim, with dry forests, in the Catimbau National Park. Five collections were performed in each area during the drought season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These bromeliads species are found in one of the largest Caatinga protected area, the Catimbau National Park, which protects about 62,294 hectares of the Caatinga forest (ICMBio 2018). Several studies have already been carried out in the Catimbau National Park with the goals of investigating its fungal diversity (Oliveira et al 2013;Maia 2014;Barbosa et al 2016;Lima et al 2016); however, fewer studies have been conducted to verify the association of endophytic fungi with the Caatinga plants.…”
Section: Introductionmentioning
confidence: 99%
“…These bromeliads species are found in one of the largest Caatinga protected area, the Catimbau National Park, which protects about 62,294 hectares of the Caatinga forest (ICMBio 2018). Several studies have already been carried out in the Catimbau National Park with the goals of investigating its fungal diversity (Oliveira et al 2013;Maia 2014;Barbosa et al 2016;Lima et al 2016); however, fewer studies have been conducted to verify the association of endophytic fungi with the Caatinga plants.…”
Section: Introductionmentioning
confidence: 99%
“…Houbraken et al 2016a; Barbosa et al 2018;Diao et al 2018;George et al 2019;Gonçalves et al 2019;. Species of Penicillium are commonly found in soil, decaying organic materials, animal feed, and stored grains, as well as indoors (Cruz et al 2013; Barbosa et al 2016Barbosa et al , 2018Houbraken et al 2016b;Yadav et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Oliveira et al,46 observed that Aspergillus and Penicillium are the most abundant genera and suggested that abiotic factors are the main source of variation in community structures. Moreover, the studies on soil fungal diversity allowed us to detect new fungal species isolated from Caatinga soils.52,53 Nascimento-Barbosa et al, 50 found that diversity and distribution of Aspergillus and Penicillium were directly affected by climate, vegetation and soil type and they pointed out that the loss of diversity was due to widespread disturbance.In a recent study, Cruz et al, 51 identified the genus Aspergillus as the most abundant isolation in some anthropic areas more than others and explained that fungal communities have changed due to anthropization. …”
mentioning
confidence: 99%